2020
DOI: 10.1101/2020.04.13.20064220
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Severe underestimation of COVID-19 case numbers: effect of epidemic growth rate and test restrictions

Abstract: To understand the scope and development of the COVID-19 pandemic, knowledge of the number of infected persons is essential. Often, the number of "confirmed cases", which is based on positive RT-PCR test results, is regarded as a reasonable indicator. However, limited COVID-19 test capacities in many countries are restricting the amount of testing that can be done. This can lead to the implementation of testing policies that restrict access to COVID-19 tests, and to testing backlogs and delays. As a result, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 10 publications
3
33
0
4
Order By: Relevance
“…Numerous assumptions have been made about the true magnitude and evolution of the epidemic around the world. It has been commonly assumed that officially reported data are underestimated [4,5], especially in Africa. The insufficient diagnostic capacity of countries and the high proportion of asymptomatic cases may explain such an underestimation [6].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous assumptions have been made about the true magnitude and evolution of the epidemic around the world. It has been commonly assumed that officially reported data are underestimated [4,5], especially in Africa. The insufficient diagnostic capacity of countries and the high proportion of asymptomatic cases may explain such an underestimation [6].…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of a radical comprehensive mental health response, we may observe a new epidemic of mental health problems and death of despair, defined as preventable death due to high-risk behaviors, like suicide and drug use. may have been systemically underestimated (Richterich, 2020). This number can reflect the minimum number of families who have lost a loved one due to COVID-19 by April 2020 ("COVID-19 CORONAVIRUS PANDEM-IC", 2020).…”
Section: Plain Language Summarymentioning
confidence: 99%
“…By the end of April 2020, more than 200,000 deaths caused by this disease were reported worldwide. The real number may be even higher as deaths may have been systemically underestimated ( Richterich, 2020 ). This number can reflect the minimum number of families who have lost a loved one due to COVID-19 by April 2020 ( “COVID-19 CORONAVIRUS PANDEMIC”, 2020 ).…”
Section: Covid-19mentioning
confidence: 99%
“…These biases are mainly due to the uncertainty in incidence data that can arise due to both the transmission characteristics of this virus (asymptomatic and pre-symptomatic transmission) and the quality and preparedness of the public health system. For COVID-19, it has been shown that the number of observed confirmed cases significantly underestimates the actual number of infections [10][11]. For instance, during the initial rapid growth phase of the COVID-19 epidemic, the number of confirmed case underestimated the actual number of infections by 50 to 100 times [10].…”
Section: Introductionmentioning
confidence: 99%
“…For COVID-19, it has been shown that the number of observed confirmed cases significantly underestimates the actual number of infections [10][11]. For instance, during the initial rapid growth phase of the COVID-19 epidemic, the number of confirmed case underestimated the actual number of infections by 50 to 100 times [10]. In France, it has been estimated that the detection rate increased from 7% in mid-May to 40% by the end of June, compared to well below 5% at the beginning of the epidemic [12].…”
Section: Introductionmentioning
confidence: 99%